2020
DOI: 10.1248/bpb.b20-00392
|View full text |Cite
|
Sign up to set email alerts
|

Germacrone Reduces Cisplatin-Induced Toxicity of Renal Proximal Tubular Cells <i>via</i> Inhibition of Organic Cation Transporter

Abstract: Cisplatin is a widely used chemotherapy for solid tumors; however, its benefits are limited by serious nephrotoxicity, particularly in proximal tubular cells. The present study investigated the renoprotective effect and mechanisms of germacrone, a bioactive terpenoid compound found in Curcuma species on cisplatin-induced toxicity of renal cells. Germacrone (50 and 100 µM) attenuated apoptosis of human renal proximal tubular cells, RPTEC/TERT1 following treatment with 50 µM cisplatin and for 48 h. Co-treating R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Germacrone plays a neuroprotective role by protecting against oxygen-glucose deprivation/reperfusion injury [ 23 ]. Germacrone reduces cisplatin-induced nephrotoxicity by inhibiting organic cation transporters [ 24 ]. Substantial evidence has shown that germacrone has strong antioxidant and anti-apoptotic effects, however, the role of germacrone in the development of DN remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Germacrone plays a neuroprotective role by protecting against oxygen-glucose deprivation/reperfusion injury [ 23 ]. Germacrone reduces cisplatin-induced nephrotoxicity by inhibiting organic cation transporters [ 24 ]. Substantial evidence has shown that germacrone has strong antioxidant and anti-apoptotic effects, however, the role of germacrone in the development of DN remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…14,15) Certain phytochemicals ameliorate cisplatin-induced neph-rotoxicity by inhibiting ROS accumulation and apoptosis. [16][17][18] Although nephroprotective effects of these phytochemicals have been reported in preclinical studies, there is still no approved drugs from phytochemicals for cisplatin's nephrotoxicity (see detail in review). 19) Current clinical practice only provides supportive treatments to recover renal function.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, terpenoids are a large and diverse group of lipids resulting from five-carbon isoprene units assembled in thousands of combinations and are isolated from plants and microbial sources. The following terpenoids have shown potential in some studies: anemoside B4 [ 126 ], carnosic acid [ 127 ], carvacrol [ 128 , 129 ], dioscin [ 130 ], germacrone [ 131 ], ginsenoside 20 (S)-RG3/Re/RG5/Rk1/Rh2 [ 132 , 133 , 134 , 135 , 136 ], linalool [ 137 ], Panax quinquefolius saponins [ 138 ], Panax notoginseng saponins [ 139 , 140 ], platycodin D [ 141 , 142 ], pseudoginsengenin DQ [ 53 ], red ginseng [ 143 ], saikosaponin D [ 144 ], and Terminalia arjuna triterpenoid saponins [ 145 ].…”
Section: Potential Utility Of Natural Products In Ddp-induced Apoptosismentioning
confidence: 99%